Curcumin inhibits autocrine growth hormone-mediated invasion and metastasis by targeting NF-kappa B signaling and polyamine metabolism in breast cancer cells - Çoker Gürkan, Ajda; Çelik, Merve; Uğur, Merve; Durdu, Zeynep Begüm; Ünsal Palavan, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (My University, 2018)
Curcumin is assumed to be a plant-derived therapeutic drug that triggers apoptotic cell death in vitro and in vivo by affecting different molecular targets such as NF-kappa B. Phase I/II trial of curcumin alone or with chemotherapeutic drugs has been accomplished in pancreatic, colon, prostate and breast cancer cases. Recently, autocrine growth hormone (GH) signaling-induced cell growth, metastasis and drug resistance have been demonstrated in breast cancer. In this study, our aim was to investigate the potential therapeutic effect of curcumin by evaluating the molecular machinery of curcumin-triggered apoptotic cell death via focusing on NF-kappa B signaling and polyamine (PA) metabolism in autocrine GH-expressing MCF-7, MDA-MB-453 and MDA-MB-231 breast cancer cells. For this purpose, a pcDNA3.1 (+) vector with a GH gene insert was transfected by a liposomal agent in all breast cancer cells and then selection was conducted in neomycin (G418) included media. Autocrine GH-induced curcumin resistance was overcome in a dose-dependent manner and curcumin inhibited cell proliferation, invasion-metastasis and phosphorylation of p65 (Ser536), and thereby partly prevented its DNA binding activity in breast cancer cells. Moreover, curcumin induced caspase-mediated apoptotic cell death by activating the PA catabolic enzyme expressions, which led to generation of toxic by-products such as H2O2 in MCF-7, MDA-MB-453 and MDA-MB-231 GH+ breast cancer cells. In addition, transient silencing of SSAT prevented curcumin-induced cell viability loss and apoptotic cell death in each breast cancer cells. In conclusion, curcumin could overcome the GH-mediated resistant phenotype via modulating cell survival, death-related signaling routes and activating PA catabolic pathway.
Keywords: Breast cancer; Growth hormone; Curcumin; NF-kappa B; Apoptosis; Polyamine; MAMMARY-CARCINOMA CELL; ESSENTIAL MEDICINAL CHEMISTRY; INDUCED APOPTOSIS; TYROSINE PHOSPHORYLATION; ENDOMETRIAL CARCINOMA; CYCLE ARREST; EPITHELIAL-CELLS; EXPRESSION; RECEPTOR; ACTIVATION